1982
DOI: 10.1128/aac.21.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antimicrobial susceptibility patterns among coagulase-negative staphylococci

Abstract: Coagulase-negative staphylococci, identified as S. epidermidis, S. saprophyticus, S. haemolyticus, S. hominis, and S. warneri, were tested for susceptibility to a number of antimicrobial agents by disk agar diffusion and broth microdilution methods, S. warneri and S. saprophyticus were found to be the most susceptible, and S. haemolyticus and S. epidermidis were found to be the least susceptible. Differences in antimicrobial susceptibility patterns are discussed, along with their epidemiological and therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 11 publications
4
17
0
Order By: Relevance
“…The MICs of penicillin G for S. saprophyticus strains in this report are similar to those noted by previous investigators (9,12) and indicate intermediate susceptibility to this agent (14). Moreover, the MIC was independent of the ability of strains to produce ,3-lactamase.…”
Section: Resultssupporting
confidence: 80%
“…The MICs of penicillin G for S. saprophyticus strains in this report are similar to those noted by previous investigators (9,12) and indicate intermediate susceptibility to this agent (14). Moreover, the MIC was independent of the ability of strains to produce ,3-lactamase.…”
Section: Resultssupporting
confidence: 80%
“…Several investigators have reported that strains of Staph. haemolyticus are significantly more resistant to antimicrobial agents than other staphylococcal species (Price & Flournoy, 1982;Gill, Selepak & Williams, 1983;Hamilton-Miller & Illiffe, 1985;Davies et al 1986;Del Bene et al 1986). In the present study, strains of Staph.…”
Section: Discussionmentioning
confidence: 99%
“…Among coagulase-negative staphylococci, tetracycline resistance, like other antibiotic resistances, is more common in S. epidermidis and S. haemolyticus than in the other species (18,19). However, tet(K) was detected in all the Tcr Mcs strains belonging to the various species studied ( (24) but also in 30% of methicillin-susceptible S. aureus strains and 5% of coagulasenegative Staphylococcus strains ( Table 1).…”
mentioning
confidence: 97%